The Dynamics of an Interorganizational Emergency Management Network: Interdependent and Independent Risk Hypotheses. - Jung, Kyujin; Song, Minsun; Park, Hyung Jun (Public Administration Review)
The purpose of this research is to uncover the dynamic structure of an interorganizational emergency management network after a disaster. This research tests two hypothesized network structures: interdependent risk and independent risk. While the former illustrates the importance of trust and information redundancy in coordinating and aligning emergency preparedness and response, the latter captures the tendency for local actors to seek dominant partners to bridge crucial information across the region. A stochastic actor‐based model with a forward selection strategy is used to analyze the structural effects of endogenous networks and the effects of exogenous community attributes on interorganizational ties. Based on the data sets collected before and after the 2012 typhoons in South Korea, the results support the interdependent risk hypothesis, suggesting that an interorganizational network structure tends to evolve into the notion of shared collaboration risk.